Problem diagnostic of Krukenberg tumor - Reza Wangsanagara; Pungky Mulawardhana; Vicky Sumarki; Anny Setijo Rahaju; Tri Wulanhandarini (Majalah Obstetri dan Ginekologi, 2019)
Objectives: to report the case of Krukenberg tumor in 57 years old woman, with complaints of abdominal enlargement since the last 10 months.Case Report: a 57 years old woman, multipara, post menopause, came to our hospital with complaints of enlarging abdomen. Abdominal physical examination showed enlarging abdomen, hard palpable mass, measured 17 cm in diameter, and limited mobility. Abdominal CT result showed solid mass of the right adnexal, expanding to upper right abdomen, omental cake, ascites, and left pleural effusion, right lobe hepatic cyst and multiple bilateral renal cysts. Patient was diagnosed as solid ovarian tumor, suspicious of malignancy. Colonoscopy revealed hemorrhoid interna. Total abdominal hysterectomy with bilateral salpingo-oophorectomy was done. Histopathologic findings showed malignant ovarian tumor, signet ring cell carcinoma of the cervics, endometrium, myometrium, nodule in gastrocolica ligament, and prevesica urinaria nodule. IHC examination of the ovarian tumor showed possible source was of colorectal, supporting the diagnosis of Krukenberg tumor with CK20 (+) and CK7 (-)Conclusion: Krukenburg tumor is a rare ovarian malignancy. Clinical symptoms usually consist of abdominal distension, pain caused by large ovarian mass. Diagnosis of Krukenburg tumor is confirmed by characteristic histologic findings of malignant signet ring cells with cellular stroma. Management for ovarian tumor is surgery removal, with very poor prognosis.